2012
DOI: 10.1002/ejic.201200935
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structuring of Ni MoS2 by using an Ionic Liquid

Abstract: To minimize air pollution resulting from exhaust gas emission, a decrease in the concentrations of the sulfur compounds in fuels has become a major issue in the last 10 years. The development of catalysts for the hydrodesulfurization process is a challenge for the oil industry. In the present work, a new and easy way to synthesize Ni-Mo-S hydrotreatment catalysts and in particular the effect of ionic liquids on the final structure was studied. It was shown that the addition of the ionic liquid [BMIM][NTf 2 ] t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Without polymer, a second phase corresponding to nickel sulfide NiS is also observed. The formation of nickel sulfide phase has already been observed in several synthesis of NiMoS catalysts [21,26,32]. This may be due to the reaction between the sulfur expelled during the thermal treatment and some Ni that is not used to form the mixed Ni-Mo-S phase.…”
Section: Samplementioning
confidence: 91%
See 1 more Smart Citation
“…Without polymer, a second phase corresponding to nickel sulfide NiS is also observed. The formation of nickel sulfide phase has already been observed in several synthesis of NiMoS catalysts [21,26,32]. This may be due to the reaction between the sulfur expelled during the thermal treatment and some Ni that is not used to form the mixed Ni-Mo-S phase.…”
Section: Samplementioning
confidence: 91%
“…For the hydrothermal synthesis of Ni-promoted MoS 2 in the presence of decalin, Yoosuk et al [25] have shown that by increasing the temperature to 375 • C and the pressure up to 2.8 MPa, a very high specific surface area up to 250 m 2 •g −1 could be obtained. Recently, we have reported a first series of data on the preparation of Ni-promoted MoS 2 catalysts in the presence of an ionic liquid and their physicochemical characterization has shown different morphologies and an increase of the specific surface area depending on the amount of ionic liquid [26].…”
Section: Of 17mentioning
confidence: 99%
“…We found a decrease of the lower BE component as the Ni amount increases, The Ni 2p 3/2 peak was separated into chemically shifted components to identify the Ni species. Three components at BEs of 853.5, 855.0, and 856.6 eV were included in the fit, which were attributed to NiS x -like structure, Ni-Mo-S structure, and NiO x species, respectively, according to the literature [52,53,[62][63][64]. Then, we analyzed the evolution of each component as a function of the Ni doping ( Figure 3E, Table S2).…”
Section: Synthesis and Physicochemical Characterizationmentioning
confidence: 99%
“…11,12 The magnetic and electronic properties of MoS 2 nanoribbons could be tuned by 3d TMs doping. Either 3d TM substrates or 3d TM nanoclusters could 35 alter the electronic structures of MoS 2 monolayer.…”
Section: Introductionmentioning
confidence: 99%